Analisa Keausan Besi Cor Kelabu dan Alumunium Ai₂O₃ dengan Pelumas SAE 40 Menggunakan Alat Uji Tribology Pin On Disc - Aries Dwi Cahyono; Anggit Bayu Prabowo; Aan Burhanudin; Hisyam Ma'mun; Ihsan Nur Roziqin (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2022)
Tribology is used for testing wear and tear materials to know the results of wear and friction. Tribology consists of pins in the shape of a ball made of certain materials needed according to our needs, and discs can also be adjusted according to the types of materials. This research aims to know the results of the comparison between the wear of cast iron and aluminum AI O₃. This study analyzes the aluminum material for the ± 13th rotation, the friction force that occurs in this condition is 0.700 gram. It decreases to 0.470 gram in this condition, and the frictional force is in a steady state. This study analyzes the Cast Iron material will be stable after passing through the 10th round. The frictional force that occurs in this condition is 0.550 grams and then decreases to 0.245 grams. The frictional force is in a steady-state condition.